Invasive lobular carcinoma with metastasis to the pectoralis muscle - Odai El-Samawi, MD; Alexander M. Satei, MBBS; Patricia A. Miller, MD (Radiology Case Reports)
A 61-year-old female presented to our breast clinic for her annual screening mammogram, which revealed an irregular, spiculated mass in the upper outer quadrant of the right breast suspicious for malignancy. Ultrasound imaging identified the mass within the upper outer quadrant of the right breast, as well as another mass within the right major pectoralis muscle, raising concern for metastatic involvement. Magnetic resonance imaging further confirmed an irregular, enhancing mass in the right upper outer breast and an area of mass enhancement in the right pectoralis major muscle. Biopsy of both lesions confirmed invasive lobular carcinoma (ILC). ILC metastasis to the pectoralis muscle is exceedingly rare, with few cases described in the literature. Our case highlights the typical and less common patterns of ILC metastasis, its imaging characteristics, and the implications for treatment and prognosis in such cases.